2021
DOI: 10.1021/acs.inorgchem.0c03520
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Design of a Frustrated Lewis Pair Containing Methyleneborane and Carbene for Dinitrogen Activation

Abstract: Activation of atmospherically abundant dinitrogen (N2) by metal-free species under mild reaction conditions has been one of the most challenging areas in chemistry for decades. Very recent but limited progress in N2 activation by boron species, including two-coordinated borylene and methyleneborane and three-coordinated borole and borane, has been made toward metal-free N2 activation. Here, we systematically probe an experimentally viable frustrated Lewis pair (FLP) containing two moieties (methyleneborane and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 91 publications
1
25
0
1
Order By: Relevance
“…A similar relation between aromaticity and activation power of FLPs was observed by Zhuang et al [97] in a DFT study on CO 2 activation. Rouf et al [98] demonstrated an increase in the reaction feasibility of dinitrogen activation by FLPs due to an increase in aromaticity. A DFT-based study performed by Trujillo et al [94] shows the effect of aromaticity in the activation power of FLPs.…”
Section: Activation Of Other Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar relation between aromaticity and activation power of FLPs was observed by Zhuang et al [97] in a DFT study on CO 2 activation. Rouf et al [98] demonstrated an increase in the reaction feasibility of dinitrogen activation by FLPs due to an increase in aromaticity. A DFT-based study performed by Trujillo et al [94] shows the effect of aromaticity in the activation power of FLPs.…”
Section: Activation Of Other Small Moleculesmentioning
confidence: 99%
“…A similar relation between aromaticity and activation power of FLPs was observed by Zhuang et al [97] in a DFT study on CO2 activation. Rouf et al [98] demonstrated an increase in the reaction feasibility of dinitrogen activation by FLPs due to an increase in aromaticity. Some reactions with FLPs were discovered a few years ago, such as Nsulfinyltolylamine (p-TolNSO) yielding a seven-membered cyclic product where binding occurs via N and O centers of p-TolNSO [46].…”
Section: Activation Of Other Small Moleculesmentioning
confidence: 99%
“…因为此方法不需要使用钌、铑、铱、钯等贵金属, 可以 有效避免金属残留和催化剂失活等问题, 目前已引起各 国科研工作者极大的研究兴趣 [19] . 截止目前, FLPs 已作 为催化剂被应用于亚胺、烯胺、烯烃、多芳香烃、炔烃、 酮和醛等不饱和化合物的氢化反应 [12,[20][21][22][23][24][25][26][27][28][29][30] ; 此外, 有报 道显示: FLPs 还能活化 N 2 、CO 2 、SO 2 、NO、CO、N 2 O 等小分子 [31][32][33][34][35] , 进一步扩展了 FLPs 化学的范畴.…”
Section: 引言unclassified
“…Aromaticity [48][49][50][51] is a fundamental concept in chemistry that usually improves the stability of compounds with a wide range of applications to singlet fission [52][53][54] as well as reaction mechanisms, e.g., N 2 activation, [55][56][57][58] C-F bond activation, 59,60 and CO 2 capture. 61 In contrast, antiaromaticity usually leads to instability.…”
Section: Introductionmentioning
confidence: 99%